Wpływ rynku ubezpieczeń na konkurencję w rolnictwie - Klimkowski, Cezary (Impact of Insurance Market on Competition in Agriculture, 2006)
Production risk is considered to be the major reason responsible for high level of income variability in agriculture. From all methods of reducing this risk purchasing insurance cover seems to be the most effective. However, only limited fraction of agricultural holdings buy insurance and agricultural insurance market remains incomplete. All over the world agricultural insurance markets are degraded by asymmetric information, systemic risk and disaster payments provided by governments. Lack of well-developed insurance markets impedes access to affordable credit and discourages farmers from implementing specialization in production, what in turn weakens farmers' incentive to cooperate among themselves. Government intervention appears to be the best solution, which can improve present situation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 419-425